Decylprodigiosin: a new member of the prodigiosin family isolated from a seaweed-associated Streptomyces - Girão, Mariana; Freitas, Sara; Martins, Teresa P.; Urbatzka, Ralph; Carvalho, Maria F.; Leão, Pedro N. (Frontiers in Pharmacology, 2024)
Bioprospecting actinobacterial secondary metabolism from untapped marine sources may lead to the discovery of biotechnologically-relevant compounds. While studying the diversity and bioactive potential of Actinomycetota associated with Codium tomentosum, a green seaweed collected in the northern Portuguese cost, strain CT-F61, identified as Streptomyces violaceoruber, was isolated. Its extracts displayed a strong anticancer activity on breast carcinoma T-47D and colorectal carcinoma HCT116 cells, being effective as well against a panel of human and fish pathogenic bacteria. Following a bioactivity-guided isolation pipeline, a new analogue of the red-pigmented family of the antibiotics prodigiosins, decylprodigiosin (1), was identified and chemically characterized. Despite this family of natural products being well-known for a long time, we report a new analogue and the first evidence for prodigiosins being produced by a seaweed-associated actinomycete.